The M&E (Monitoring & Evaluation) Universe - INTRAC (INTRAC, 2019)
The M&E Universe is a free, online resource developed by INTRAC to support development practitioners involved in monitoring and evaluation (M&E). It consists of a series of short papers (2-6 pages) on different subjects related to M&E. To begin exploring the Universe right away, use the button below. To find out more, read on.

Supporting users with the OutNav approash - Matter of Focus (2019)
This report has been generated in OutNav, using the theory-based approach to evaluation pioneered by Matter of Focus. Example of a report from the tool, explaining OutNav approach